Parties of Order Right and Left - Clover, Joshua (Identities: Journal for Politics, Gender and Culture, 2022)
“Parties of Order Right and Left” takes the right-authoritarian turn (particularly in Central Europe) as an opportunity to reflect on the left-authoritarian turn elsewhere in Europe and “the West” more broadly. The talk pays special attention to the shared faith in policy imposition as the necessary and sufficient mechanism to address social volatility, notably the volatility both expressed and borne by surplus populations and climate refugees. The presupposition of policy solutions even in times of social catastrophe is traced through two parallel texts, Andreas Malm’s How to Blow Up a Pipeline and Kim Stanley Robinson’s Ministry for the Future, and their shared theory of political violence as policy weapon. It concludes with a discussion regarding the nationalist implications of policy solutions more broadly and the historically specific demand for internationalism against border regimes in present conditions. Author(s): Joshua Clover Title (English): Parties of Order Right and Left Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 19, No. 1-2 (2022). Publisher: Institute of Social Sciences and Humanities - Skopje Page Range: 28-38 Page Count: 10 Citation (English): Joshua Clover, "Parties of Order Right and Left,” Identities: Journal for Politics, Gender and Culture, Vol. 19, No. 1-2 (2022): 28-38. Author Biography Joshua Clover, University of California Davis Joshua Clover is the author of seven books, including Roadrunner (Duke, 2021) as well as Riot.Strike.Riot: the New Era of Uprisings, a political economy of social movements, with recent editions in Italian, French, German, Turkish, and Swedish. He is a currently professor of English and Comparative Literature at University of California Davis as well as Affiliated Professor of Literature and Modern Culture at University of Copenhagen.